2007
DOI: 10.1038/sj.npp.1301598
|View full text |Cite
|
Sign up to set email alerts
|

Acute Tryptophan Depletion in Healthy Volunteers Enhances Punishment Prediction but Does not Affect Reward Prediction

Abstract: Central serotonin (5-HT) has been implicated in emotional and behavioral control processes for many decades, but its precise contribution is not well understood. We used the acute tryptophan depletion procedure in young healthy volunteers to test the hypothesis that central 5-HT is critical for predicting punishment. An observational reversal-learning task was employed that provided separate measures of punishment and reward prediction. Under baseline, subjects made more prediction errors for punishmentassocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
154
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(182 citation statements)
references
References 65 publications
22
154
4
Order By: Relevance
“…From this perspective, loss chasing can be viewed as an aversively motivated escape behavior, but one controlled, at least in part, by the marginal utility of continued play relative to its cessation. Our finding that tryptophan depletion reduced our behavioral model of loss chasing suggests that, in this instance at least, diminished central serotonin activity reduced the marginal utility of continued play by increasing the salience of future bad outcomes across the range of values encountered during the game (Cools et al, 2008;Deakin and Graeff, 1991).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…From this perspective, loss chasing can be viewed as an aversively motivated escape behavior, but one controlled, at least in part, by the marginal utility of continued play relative to its cessation. Our finding that tryptophan depletion reduced our behavioral model of loss chasing suggests that, in this instance at least, diminished central serotonin activity reduced the marginal utility of continued play by increasing the salience of future bad outcomes across the range of values encountered during the game (Cools et al, 2008;Deakin and Graeff, 1991).…”
Section: Discussionmentioning
confidence: 86%
“…By contrast, serotonin activity also plays a significant role in learning from, and coping with, aversive events (Bari et al, 2010;Daw et al, 2002;Deakin and Graeff, 1991;Evers et al, 2005). Given that tryptophan depletion can also improve the prediction of punishing outcomes (Cools et al, 2008), and enhance neural responses to punishing outcomes within the anterior cingulate cortex (Evers et al, 2005), we also anticipated that tryptophan depletion might increase the salience of bad outcomes and diminish loss-chasing behavior. In fact, while producing no marked changes in healthy adults' state affect, tryptophan depletion significantly reduced the proportion of decisions participants made to chase losses, and reduced the number of consecutive decisions to chase, during a run of losing gambles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, if serotonin activity can influence the activity of positive vs negative cognitive biases, it should not surprise that tryptophan depletion and other manipulations that enhance such biases find greater expression in the processing of negative choice outcomes (Cools et al, 2008b;Dayan and Huys, 2008), as aversive events more frequently warrant reappraisal. Indeed, this proposal is reminiscent of an older theory suggested that activity of the dorsal raphe nucleus might mediate coping responses to such events (Deakin, 1998;Deakin and Graeff, 1991), and that variation in the functioning of the ascending serotonin system confers vulnerability to psychological disorders involving depression and anxiety (Deakin and Graeff, 1991).…”
Section: Serotonin and The Idea Of 'Appraised' Valuesmentioning
confidence: 99%
“…Accordingly, the majority of studies on cognitive and affective processing in depressed patients highlight strong biases toward negative stimuli and away from positive ones, which interfere with normal cognitive functioning (Elliott et al, , 1997Gotlib et al, 2004;Murphy et al, 2003;Roiser et al, 2009;Siegle et al, 2001), whereas long-term treatment with selective serotonin reuptake inhibitors (SSRIs) counteracts these biases. Moreover, lowering brain content of 5-HT by acute tryptophan depletion (ATD) in healthy subjects causes similar biases in neuropsychological tasks assessing affective decisionmaking and punishment prediction (Cools et al, 2008b;Murphy et al, 2002;Rogers et al, 2003;Roiser et al, 2006). In addition, in rats and other animals, 5-HT modulates the processing of aversive stimuli (Burghardt et al, 2004;Dayan and Huys, 2009;Inoue et al, 2004;Stutzmann and LeDoux, 1999;Wilkinson et al, 1995).…”
Section: Introductionmentioning
confidence: 99%